Effect of local anesthetics on renal function: An animal study in Iran - Rasul Gheisari; Masoud Saatchi; Firoozeh Estakhri; Mehrdad Vossoughi; Mohammad Bazaei; Zahra Khosravani (Wolters Kluwer Medknow Publications, 2023)
Background: Although most of the metabolism of local anesthetics (LAs) takes place in the liver, no study has investigated the effect of these anesthetics on the kidney function of single-kidney humans or animals. The present study was conducted to examine the effect of LAs on renal function in single-kidney rats. Materials and Methods: The present experimental animal study with two control groups was done in an animal laboratory. Forty-two rats were randomly assigned to seven groups of six rats, including two control groups and five experimental groups. The experimental groups underwent intraperitoneal anesthesia with 2% lidocaine, 2% lidocaine with 1:80,000 epinephrine, 4% articaine, 3% prilocaine with 0.03 IU Felypressin, and 3% mepivacaine, respectively. Unilateral nephrectomy was done. After 24 h, the rats' blood urea nitrogen (BUN), serum creatinine (Cr), and blood specific gravity (BSG) were measured. A standard dose of anesthetics was injected into the peritoneum for 4 days afterward. Then, these indices were measured again 24 h after the last injection. Data were analyzed using IBM SPSS (version 21.0). One-way analysis of variance, Tukey's honestly significant difference post hoc, and paired t-tests were used for statistical analysis. P < 0.05 was considered statistically significant. Results: The results indicated significant differences among groups in the rats' BUN and serum Cr 24 h after nephrectomy (P < 0.05). However, there were no significant differences in BUN, BSG, and Cr among groups after the interventions. Conclusion: LAs did not affect renal function in single-kidney rats. Therefore, dentists can use the anesthetics in single-kidney people.